Edukasi Dan Inovasi Untuk Masa Depan Yang Lebih Cerah - Rosalia, Ananda Riza; Arifa, Diah Anindya; Arryanto, Bimamrulloh Dhimas; Fajri, Wildan; Khomeini, Khomeini; Rachman, Renandri Abdillah; Asih, Trinia Sefti; Kholik, Fikri Abdul; Latif, Muhammad Ghafar; Akmalia, Lila Maisya; Alifi, Fasyandira Gresila Sekar; Suryanto, Suryanto (Universitas Muhammadiyah Yogyakarta, 2025)
This program is a form of community service aimed at developing the community's potential and improving its welfare. The community service program is located in Dusun Suropati, Hargotirto Village, Kokap District, Kulon Progo Regency, Special Region of Yogyakarta. It focuses on three main programs: Dusun Bersinar (Drug-Free Hamlet), Pasar Online Kampung (Village Online Market), and Bincang Parenting dan Stunting (Parenting and Stunting Discussion). This program aims to create a healthy, safe, and productive environment. The Dusun Bersinar (Drug-Free Hamlet) program seeks to enhance public knowledge about the dangers of drugs, their health impacts, and legal consequences. This activity is carried out through public education and counseling under the theme